Evaluation of warehousing productivity performance indicators by the FAHP method - Karim, Nur Hazwani; Abdul Rahman, Noorul Shaiful Fitri; Md Hanafian, Rudiah; Mohd Saifudin, Adam; Ismail, Alisha; Saharuddin, A.H.; Abd Kader, Ab Saman; Muda, Mohd Shaladdin (2020)
A warehouse is an important component in logistics operation as it is a huge contributor to speed up and cost the supply chain management.To monitor the performance of the warehouse operation, management will analyse the measurement of warehousing productivity. The basis of measuring productivity performance in the warehouse is based on how much it cost to perform an operation by utilising the warehouse resources. The purpose of this paper is to rank the most important warehouse productivity indicator for improving the warehouse operation efficiency. By indicating the main warehouse resources and its sub-criteria, a hierarchy structure of ratio-based warehousing productivity performance indicators is constructed. It presents an empirical methodology of the fuzzy analytical hierarchy process (FAHP) method, an integration between the fuzzy logic method with an analytical hierarchy process (AHP) method. The results indicate that Warehouse Management System scores the highest weight value which followed by Storage Space Utilisation and Throughput accordingly. This contributes to grab more attention on the utilization of technologies into the warehouse operation. This article also identifies several additional research opportunities on warehouse performance evaluation assessment.